2019
DOI: 10.26699/jnk.v6i3.art.p292-299
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kadar Ureum, Hemoglobin dan Lama Hemodialisa dengan Kualitas Hidup Penderita PGK

Abstract: Penderita penyakit ginjal kronik mengalami penumpukan produk sisa dalam darah khususnya ureum yang menjadi toksin bagi tubuh. Anemia pada pasien PGK menyebabkan badan lemah dan penurunan perfusi jaringan. Terapi hemodialisa bisa menjadi stresor bagi pasien, karena terapi ini memerlukan waktu yang lama, keadaan ini berpotensi menurunkan kualitas hidup pasien. Tujuan penelitian adalah mengetahui hubungan kadar ureum, hemoglobin dan lama hemodialisa dengan kualitas hidup penderita PGK di Ruang Hemodialisa RS dr S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…With this condition, patients feel their QoL is significantly reduced. 26 This research showed no relationship between urea levels and the QoL of hemodialysis patients at Roemani Hospital, Semarang. This result could occur because the amount of data is different, where there is only 1 respondent who has normal urea levels.…”
Section: Variablementioning
confidence: 69%
“…With this condition, patients feel their QoL is significantly reduced. 26 This research showed no relationship between urea levels and the QoL of hemodialysis patients at Roemani Hospital, Semarang. This result could occur because the amount of data is different, where there is only 1 respondent who has normal urea levels.…”
Section: Variablementioning
confidence: 69%
“…The characteristics of urine can be determined through its color, transparency, and odor. Since urine exhibits different levels of color, detecting urea often employs colorimetric techniques for medical diagnosis [3,4,5]. Colorimetry is an analytical method based on color changes to ascertain the concentration of substances in a sample [6,7].…”
Section: Introductionmentioning
confidence: 99%